Analisis Dampak Pemasangan Zero Point Clamping System Terhadap Efektivitas Mesin CNC Milling 5 Axis Dengan Metode Overall Equipment Effectiveness - Antari, Muhammad Aiman; Hendaryanto, Ignatius Aris; Handoko; Winarno, Agustinus (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
The manufacturing industry sector in Indonesia is experiencing rapid development, significantly contributing to the national GDP. CNC milling 5-axis technology, offering high accuracy and efficiency, is increasingly being used across various industries. However, clamping process issues often hinder the optimal performance of these machines. This study analyzes the impact of implementing the Zero Point Clamping System on the effectiveness of CNC milling 5-axis machines using the Overall Equipment Effectiveness (OEE) method. The study results show a significant increase in the Availability value, which rose by 10.7% from 80.3% to 91%, and the Performance Rate, which increased by 2.9% from 93.4% to 96.3%, while the Quality Ratio remained unchanged. This improvement led to the OEE value increasing from 75% to 87.5%, indicating a 12.5% increase in effectiveness. The implementation of the Zero Point Clamping System significantly reduced Setup and Adjustment time from 13.8% to 4.7% and Idling and Minor Stoppage time from 5.9% to 4.4%, as well as reducing Reduced Speed Losses from 5.25% to 3.5%. These results demonstrate that the application of the Zero Point Clamping System can enhance the effectiveness of CNC milling 5-axis machines by reducing downtime and increasing machine speed, resulting in higher availability and improved machine performance. Consequently, this innovation makes a tangible contribution to improving operational efficiency and the competitiveness of Indonesia's manufacturing industry. Keywords: CNC milling 5 axis, Effectiveness, Overall Equipment Effectiveness, Zero Point Clamping System